Status of Laboratory Resources and Teaching Competence in Schools Division of Ilocos Norte - Gonzales, Xylene Gail I.; Cabrera, Rhea M.; Calzada, Marc Paul T. (Future Science / FSH-PH Publications, 2025)
This study examined the status of laboratory resources in public sec-ondary schools in Ilocos Norte and evaluated science teachers’ labora-tory competence. Using a descriptive survey design, the study involved 198 science teachers, selected through total enumeration method. Conducted in October 2024 at all public secondary schools in the Schools Division of Ilocos Norte, data were collected using a survey questionnaire instrument and analyzed using frequency count, per-centages, and mean for the availability and accessibility of laboratory equipment and facilities and the level of laboratory competence of teachers. Key areas investigated included the accessibility of laborato-ry facilities and equipment, the presence of laboratory technicians, and teachers’ proficiency in laboratory knowledge and instructional skills. Results revealed significant gaps in providing advanced laboratory apparatus, although basic equipment was relatively accessible. Science teachers demonstrated average competence, but challenges such as insufficient resources, inadequate training, and poor facility mainte-nance impeded optimal instruction. Notable constraints included in-frastructure issues, unequal resource distribution, and limited profes-sional development opportunities. The findings highlight the need for equitable resource allocation and enhanced competencies to improve the quality of science instruction. Recommendations include regular professional development, improved resource accessibility, and insti-tutional support to foster innovative teaching practices.